- #1
- 24
- 0
Hi I am 14 and attempting to learn calculus I have just proved product rule and am beginning examples of how it might work. Could anyone check, I will write my process.
[tex]y(x)=(12x^6)(7x^4+6)=[/tex]
[tex](12x^6)'(7x^4+6)+(12x^6)(7x^4+6)'=[/tex]
[tex](72x^5)(7x^4+6)+(12x^6)(28x^3)=[/tex]
[tex]504x^9+432x^5+336x^9=[/tex]
[tex]y(x)=840x^9+432x^5[/tex]
[tex]y(x)=(12x^6)(7x^4+6)=[/tex]
[tex](12x^6)'(7x^4+6)+(12x^6)(7x^4+6)'=[/tex]
[tex](72x^5)(7x^4+6)+(12x^6)(28x^3)=[/tex]
[tex]504x^9+432x^5+336x^9=[/tex]
[tex]y(x)=840x^9+432x^5[/tex]